P061 Response to anti-α4β7 therapy in Ulcerative colitis is associated with lymphoid aggregate attrition through impaired recruitment of naïve lymphocytes. (30th January 2023) - Canales-Herrerias, P; Uzzan, M; Seki, A; Czepielewski, R S; Verstockt, B; Dunn, A; Dai, D; Ko, H M; Furtado, G C; Tokuyama, M; Tankelevich, M; Meringer, H; et al.
Abstract: Background: Vedolizumab (VDZ) is a frontline drug for Ulcerative colitis (UC) and Crohn's disease (CD) that targets integrin α4β7, a gut-homing receptor. Despite significant use, the mechanism(s) of action (MOA) of VDZ remain unclear. Methods: Peripheral blood mononuclear cells (PBMC) from UC patients (n=43) and paired intestinal biopsies in a subset (n=12) were examined at week 0 (pre-infusion) and 14, by multiparameter flow cytometry (FC). TNF inhibitor (TNFi)-treated UC patients served as controls. Drug MOA was further examined in detail in murine models using single-cell RNA-seq, FC, conventional and immunofluorescent microscopy (IF). Photoconvertible (Kikumi) mice were used to study cellular trafficking after anti-α4β7 (DATK32) antibody (mAb) administration. Two distinct UC cohorts (n=42 and n=21 respectively) were used to correlate GI immune alterations following VDZ with mucosal healing. Results: A significant decrease of colonic and ileal naïve B and T cells was noted in VDZ- but not in TNFi-treated patients (Fig 1A), while total T cell-frequencies were unchanged. Circulating gut-homing plasmablasts (β7+) were significantly decreased post-VDZ. Peyer's patches (PP) in anti-α4β7-treated mice showed a rapid loss of cellularity associated with decreased follicular naïve B cells (Fig 1B). Single-cell RNA-seq also demonstrated a significant loss of follicular B cells, including a unique population of epithelium-associated B cells following anti-α4β7 mAb. In Kikumi mice, anti-α4β7 mAb impaired non-photoconverted follicular B cells and T cells into photoconverted PPs (Fig 1C) demonstrating that loss of PP cellularity was due to impaired cellular ingress. In VDZ-treated (but not TNFi-treated) UC patients, lymphoid aggregate (LA) size was significantly reduced in treatment responders compared to non-responders (defined by absence of histological inflammation). A distinct validation cohort further confirmed that reduced lymphoid aggregate size was associated with response to VDZ-therapy (Fig 1D). Conclusion: VDZ is associated with impaired ingress of naïve B and T cells, resulting in attrition of intestinal LA. Reduced LA size is associated with VDZ response. Immune inductive site targeting represents a novel MOA of VDZ in patients with UC.